"It put control back onto my family situation": family experiences of positive behaviour support. Issue 3 (12th June 2019) - Botterill, Sinead; Cottam, Susan; Fowke, Alex; Theodore, Kate
Abstract : Purpose: Positive behaviour support (PBS) is currently considered best practice for managing challenging behaviour in young people with intellectual and developmental disabilities. A key principle of PBS is that all members of the person's support network participate in the assessment and intervention. It is, therefore, important to understand what factors act as facilitators or barriers to family engagement; however, research in this area is limited. The purpose of this paper is to conduct a novel piece of qualitative research analysis into experiences of family members of young people who have received family-based PBS. Design/methodology/approach: Eight parents of a young person with an intellectual or developmental disability who had received PBS were interviewed about their experiences and factors they found helpful and hindering in terms of their engagement. Thematic analysis allowed a detailed and robust interpretation of the qualitative data. Findings: Five superordinate themes were identified, namely, PBS is more than just strategies, considering the family context, the therapist/family relationship, acknowledging challenges and the ongoing nature of the problem and supporting family member change. Research limitations/implications: Although research was rigorously conducted, the small sample size mean findings should be considered preliminary. Originality/value: The literature related to family engagement in PBS is limited and largely based on the opinions of professionals. This study identified factors that parents themselves felt were helpful and hindering in terms of their engagement and offers practical suggestions for services and future research.